Human Rights Perspective in Breaking the Principle of Non-Retroactiveness in Terrorism Crime Actors in Indonesia - Annisa, Sigma Febby (Lex Scientia Law Review, 2017)
As guarantees for human rights, the principle of legality and the principle of not being retroactive (non-reactive) is an important basis for law enforcement in Indonesia. This is because the law is not implemented based on the perception of the authorities or the regime, but based on statutory regulations that emerge from existing community agreements. The breakthrough of the principle of non-reactivity for perpetrators of criminal acts of terrorism, especially in the Bali Bombing I case, has generated a lot of debate. This paper tries to see how the study of the breakthrough of this principle from the perspective of human rights is a form of protection of basic human rights.